Reducing care burden and improving adherence to health-promoting behaviors among family caregivers of patients with multiple sclerosis through a healthy lifestyle empowerment program - Abdolsamad Homayouni; Parvaneh Vasli; Fatemeh Estebsari; Maliheh Nasiri (BMC, 2022)
Abstract Background and aim The chronic, progressive nature of multiple sclerosis (MS) demands long-term family-centered care for patients. In view of that, inadequate education and support provided for the family caregivers (FCGs) of MS patients increase their care burden (CB) and affect their lifestyle. This study aimed to investigate the impact of a healthy lifestyle empowerment program (HLEP) on CB and adherence to health-promoting behaviors (HPBs) in the FCGs of patients suffering from MS. Methods In this experimental study with parallel groups, conducted in Iran in 2020, a total of 60 FCGs of MS patients were recruited, and then randomized into intervention (n = 30) or control (n = 30) groups. The intervention program, the HLEP, was thus implemented virtually via WhatsApp in the intervention group upon coordinating with the MS Association in the city of Yasuj, Iran, and selecting the participants. The data were collected at three stages, including baseline, follow-up 1 (immediately after the HLEP), and follow-up 2 (three months after HLEP). The research tools were a 14-item demographic survey questionnaire, the 24-item Caregiver Burden Inventory, and the 52-item Health-Promoting Lifestyle Profile-II. Independent-samples t-test, repeated measures analysis of variance, and a linear mixed model were further used for statistical analyses, considering the significant level of 0.05. Results The study results revealed a significant decrease in the CB scores from the baseline to the follow-up 2 (77.03 ± 15.76 to 42.33 ± 12.37), and a significant increase in the values of adherence to HPBs from the baseline to the follow-up 2 (123.53 ± 14.01 to 148.06 ± 15.04) were obtained in the intervention group (p < 0.001). The linear mixed model also showed that the significant absolute changes in the scores of CB and adherence to HPBs during the follow-ups in the intervention group, compared to those in the controls, were − 8.92 and 16.47 units, respectively (p < 0.001). Conclusion Health care managers, planners, and providers are highly recommended to start developing and implementing various HLEPs for reducing CB and improving adherence to HPBs among the FCGs of patients with MS.